Analisis Kemampuan Pemahaman Konsep Matematika Kelas VII SMP Negeri 7 Padangsidimpuan Melalui Pemanfaatan Media Audio Visual Pada Materi Bilangan Bulat - Nurhaida; Puspa Riani Nasution; Haritsah Hammamah Harahap (Jurnal Cermatika, 2024)
This study aims to determine students' conceptual understanding after using audio-visual media on the topic of integer operations, using five indicators of mathematical conceptual understanding in Class VII 3 at SMP N 7 Padangsidimpuan. This research is qualitative in nature. The data in this study were obtained from direct observations, interviews with teachers, and interviews with students. After the data were collected, they were analyzed using three stages: data reduction, data presentation, and verification or conclusion drawing. Data validity was checked using data source triangulation. The subjects of this study were two Class VII teachers and 26 students from Class VII 3. The results of this study show that after learning using audio-visual media, some students experienced an improvement in their conceptual understanding. This improvement was observed across all indicators of conceptual understanding. Most students demonstrated a good understanding of integer operations, although a small number of students still struggled with this concept.